Answer:
w = -44
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
-w - 2 = 42
Step 2: Solve for w
- Add 2 to both sides: -w = 44
- Divide -1 on both sides: w = -44
Step 3: Check
Plug in w into the original equation to verify it's a solution.
- Substitute in w: -(-44) - 2 = 42
- Multiply: 44 - 2 = 42
- Subtract: 42 = 42
Here we see that 42 does indeed equal 42.
∴ w = -44 is the solution to the equation.